La conception de la villa rustica chez Caton. Entreprise agricole oú simple ferme rurale? - El Bouzidi, Saïd (Gerión. Revista de Historia Antigua, 2003)
It was not by chance that the Latin agronomists have stressed upon the purchase norms and the management patterns regarding the villa rustica as early as the llnd century AD. It was the Caton’s injunctions that basically helped to give a big spring to the villa rustica in order to incarnate other roles which responded better to the new era that was characterizing Roma with regard to it expansion in the Mediterranean area the villa were then performing other functions than the agricultural production. and thus we can single out the foundations of the agricultural enterprise having as a target of the space and the man.